Ho Chi Minh's ideology on national values and the issue of building national values in Vietnam today - Quang Dung, Trinh (Edelweiss Applied Science and Technology, 2024)
President Ho Chi Minh did not use the term “national value system,” but the content of this concept was profoundly addressed by him from a comprehensive and revolutionary perspective. During his leadership of the national liberation revolution and the building of the transitional period to socialism in Vietnam, Ho Chi Minh developed thoughts and ideas that reflected the values within the national value system. These thoughts of Ho Chi Minh have served as the foundation, worldview, and methodological orientation for Vietnam in constructing its current national value system. This article analyzes Ho Chi Minh's conception of the national value system, thereby raising the issue of the necessity and outlining some fundamental aspects of building Vietnam's national values today.